Agreement between RAPD, API20C AUX, CHROMagar Candida and microculture on oral Candida identification - Emanuene Galdino Pires; Edimilson Martins de Freitas; Paulo Rogério Ferreti Bonan; Sérgio Avelino Mota Nobre (Universidade Estadual de Campinas, 2015)
Aim: To measure the agreement of methods for identification of Candida species in oral cavity samples, comparing the CHROMagar Candida, microculture, API 20C AUX and RAPD techniques. Methods: Ninety-one colonies of Candida were isolated and presumptively identified in CHROMagar Candida, submitted to microculture, API 20C AUX and RAPD techniques. After this, agreement among methods using Kappa test was performed. Results: Agreement rates between RAPD and CHROMagar Candida, showed significant accuracy for C. albicans, C. tropicalis, C. dubliniensis and C. krusei (Kappa: 0.760, 0.640, 0.416 and 0.360, respectively, p<0.05). Comparing RAPD results with microculture, the highest agreement was for C. albicans (Kappa: 0.851 - p<0.05) but no significant agreement for C. lusitaniae, C. krusei and C. guilliermondii was obtained (p>0.05). The agreement was significant for all identified species when RAPD (OPE-18) and API 20C AUX (p<0.05) were used. Critical levels of agreement between RAPD and microculture were observed when C. lusitaniae, C. krusei and C. guilliermondii were identified. Conclusions: API 20C AUX presented the best agreement with molecular random identification and CHROMagar showed good agreement for C. albicans, C. tropicalis, C. dubliniensis and C. krusei identification.